Mechanical Engineers Handbook : Instrumentation, Systems, Controls, and Mems Book 2 - KUTZ, Myer (John Wiley and Sons, 2006)
Mechanical Engineers Handbook : Instrumentation, Systems, Controls, and Mems Book 2